SANG HYANG SAMBAH DALAM NGUSABHA SAMBAH DI DESA PAKRAMAN PESEDAHAN, MANGGIS, KARANGASEM: (Kajian Bentuk Fungsi dan Makna) - Ida Bagus Putu Eka Suadnyana (Sanjiwani: Jurnal Filsafat, 2018)
The use of Sang Hyang Sambah in Ngusabha Sambah ceremony in the village of Pakraman Pesedahan is very unique, as one of the means that support the implementation of religious ceremony based on the five basic forms of practice namely: iksa, sakti, village, kala, and tattwa so there are various forms and functions of upakara variety. Sang Hyang Sambah in Ngusabha Sambah ceremony in the village of Pakraman Pesedahan in addition to having its own characteristics, also contains value for the community supporters so that its use is maintained until now. Theories used to solve this research problem are structural functional theory, value theory and cognitive theory. This research is in the form of qualitative design. Based on the analysis, obtained the conclusion as the result of research, as follows: (1) Sang Hyang Sambah is one of the means in Ngusabha Sambah ceremony in the village of Pakraman Pesedahan. Sang Hyang Sambah shaped pelinggih made of plant material and made before the ceremony Ngusabha Sambah. (2) Sang Hyang Sambah in the process of Ngusabha Sambah ceremony has a ceremonial function as a form of sacrifice that is a religious function as a tool to cultivate belief in God, and social function to enhance a sense of togetherness. (3) The meaning that is contained in Sang Hyang Sambah in Ngusabha Sambah ceremony among others tattwa seen in people’s belief in Ida Sang Hyang Widhi Wasa, ethics is reflected in the attitude.